Subarctic soil carbon losses after deforestation for agriculture depend on permafrost abundance. (5th July 2022) - Peplau, Tino; Schroeder, Julia; Gregorich, Edward; Poeplau, Christopher
Abstract: The northern circumpolar permafrost region is experiencing considerable warming due to climate change, which is allowing agricultural production to expand into regions of discontinuous and continuous permafrost. The conversion of forests to arable land might further enhance permafrost thaw and affect soil organic carbon (SOC) that had previously been protected by frozen ground. The interactive effect of permafrost abundance and deforestation on SOC stocks has hardly been studied. In this study, soils were sampled on 18 farms across the Yukon on permafrost and non‐permafrost soils to quantify the impact of land‐use change from forest to cropland and grassland on SOC stocks. Furthermore, the soils were physically and chemically fractionated to assess the impact of land‐use change on different functional pools of SOC. On average, permafrost‐affected forest soils lost 15.6 ± 21.3% of SOC when converted to cropland and 23.0 ± 13.0% when converted to grassland. No permafrost was detected in the deforested soils, indicating that land‐use change strongly enhanced warming and subsequent thawing. In contrast, the change in SOC at sites without permafrost was not significant but had a slight tendency to be positive. SOC stocks were generally lower at sites without permafrost under forest. Furthermore, land‐use change increased mineral‐associated SOC, while the fate of particulate organic matter (POM) after land‐use change depended on permafrost occurrence. Permafrost soils showed significant POM losses after land‐use change, while grassland sites without permafrost gained POM in the topsoil. The results showed that the fate of SOC after land‐use change greatly depended on the abundance of permafrost in the pristine forest, which was driven by climatic conditions more than by soil properties. It can be concluded that in regions of discontinuous permafrost in particular, initial conditions in forest soils should be considered before deforestation to minimize its climate impact. Abstract : Climate change encourages agricultural expansion into subarctic regions and fosters deforestation. We examined the effect of land‐use change from forest to cropland and grassland on soil organic carbon (SOC) stocks and fractions, by sampling 18 farms in the discontinuous permafrost of Yukon, Canada. We found significant losses of SOC, when permafrost soils were taken into agricultural use, while no significant change in SOC stock could be observed in permafrost‐free soils.